CEO confidence bias and strategic choice: A general framework - Elizabeth Schroeder; Carol Horton Tremblay; Victor J. Tremblay (Journal of Applied Economics, 2022)
An owner of a firm may choose to hire an unbiased CEO or one with confidence bias. We develop a model that demonstrates that the owner's optimal choice depends on whether the firm and rival choice variables are strategic substitutes or strategic complements. When choice variables are strategic substitutes or strategic complements for both firms, owners optimize by hiring overconfident CEOs. When choice variables are substitutes for one firm and complements for the rival firm, each firm optimizes by hiring an underconfident CEO. We show that the model applies to price and output competition, advertising, research and development spending, and product design.
Keywords: 330; Behavioral economics; confidence bias; firm behavior; managerial overconfidence; strategic substitutes and complements